Case report: Thoracic and lumbar plasma cell myeloma mimicking hemangiomas on MRI and 18F-FDG PET/CT - Hu, Xianwen; Xiong, Wei; Li, Shun; Li, Xue; Cai, Jiong; Wang, Pan; Li, Dandan (Frontiers in Medicine, 2022)
Plasma cell myeloma (PCM) is a malignant clonal disease of abnormal proliferation of plasma cells, which is the second most common hematological malignancy after leukemia. PCM often diffuse and involve the whole body bones, especially the spinal column, ribs, skull, pelvis and other axial bones and flat bones. Herein, we present a 55-year-old man who came to the hospital seeking medical help for low back pain and numbness in his lower limbs. Computed tomorgraphy (CT) was performed because the clinician suspected that the patient had a herniated disc and the results showed that the 7th thoracic vertebrae and the 3rd lumbar vertebrae showed a low density of bone destruction with a “fence-like” change. Magnetic resonance imaging (MRI) showed that the corresponding lesions presented long T1 and long T2 signals, and the lesions were significantly enhanced in contrast-enhanced T1WI sequences, and fluoro18-labeled deoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) showed mild radioactive uptake in the lesions. Based on these imaging findings, the patient was considered for a diagnosis of hemangiomas, and surgery was performed because the affected vertebra was pressing on the spinal cord. However, intraoperative frozen section examination showed that the patient had plasma cell myeloma. Our case study suggests that PCM involving a single thoracic and lumbar spine is rare and should be considered as one of the imaging differential diagnoses of hemangiomas. Moreover, the diagnosis of PCM is difficult when the number of lesions is small, especially when the plasma cell ratio is within the normal reference range in laboratory tests.